Intensive English Instruction in Pesantren (Study on Pondok Pesantren Puncak Darus Salam, Potoan Daja Palengaan Pamekasan) - Mohammad Muchlis Solichin (OKARA: Jurnal Bahasa dan Sastra, 2018)
Various pesantren response to the challenge of moderation. One of which is Puncak Darus Salam Pesantren that implement and perform formal education coupled with the establishment of English learning. This paper aims to find 1) the reason of the leader of Pesantren Puncak Darus Salam in organizing the English teaching-learning, and 2) English teaching-learning process in Pondok Pesantren Puncak Darus Salam, Potoan Daja, Palengaan, Pamekasan. This study is qualitative and descriptive. In collecting data, the researcher use observation with non-participant, data were also collected through in-depth interviews and the documentation. Data analysis was used involves 1) data reduction, 2) data display, and 3) conclusions and verification. The research results are 1) The rational reason for the development of learning English is religious reason, that English is seen as a language that can be used for propaganda/ Da’wah of Islam, because of its position as an international language. 2) Development of English learning organized by a specialized organization namely Darwis to use traditional and student-centered learning approach, active learning methods in a regular time each day. 3) Learning English emphasizes the mastery of writing and speaking competence.